4a-4c+ac-a^2 ;
4*(a-c)-a*(a-c) ;
(a-c)*(4-a) ;
Если a=3,5 , c=-1,5 то
(3,5-(-1,5))*(4-3,5) ;
(3,5+1,5)*(0,5) ;
5*0,5=2,5.
Ответ: 2,5.
Автор:
rolandcalhoun4а -4с+ас-а^2 = 4(а-с) +а(с-а)= 4(а-с)-а(а-с)= (а-с)(4-а)
При а=3,5 и с= -1,5
(3,5+1,5)(4-3,5)=5*0,5=2,5
Ответ: 2,5
Автор:
tippy68Добавить свой ответ
Предмет:
АлгебраАвтор:
carsencuevasОтветов:
Смотреть
Предмет:
МатематикаАвтор:
adalynmontoyaОтветов:
Смотреть
Предмет:
МатематикаАвтор:
garfield81Ответов:
Смотреть
Предмет:
МатематикаАвтор:
cassiscarrollОтветов:
Смотреть